Improved Thermal Network Method for Fuel Transient Temperature Prediction of High-Speed Aircrafts - CHENG Xianda, ZHENG Haoran, YANG Xuesen, DONG Wei (Shanghai Jiaotong Daxue xuebao, 2023)
The low simulation efficiency of three-dimensional transient calculation makes it difficult to be applied in predicting fuel temperature during the entire fuel consumption process. In order to satisfy the requirements of fuel temperature field calculation in the rapid iterative fuel system design process, a novel efficient and accurate improved thermal network method was proposed. The mixing coefficient was introduced to the heat conduction equation to represent the heat convection inside the fuel, and the heat transfer caused by the mass transfer term was added to the heat balance equation to represent the problem of overall fuel flow. Based on the improved thermal network method, the transient thermal analysis model of the high-speed aircraft fuel tank was constructed. The results show that under different thermal boundary conditions and tank geometries, the temperature deviation between the thermal network method and the computational fluid dynamics(CFD) method is less than 5%, and the calculation efficiency of the thermal network method is much higher, which can greatly improve the computational efficiency. By combining CFD calculation with the improved thermal network method, a novel fuel transient temperature prediction method is provided for the design of the high-speed aircraft fuel storage system.